2010
DOI: 10.1038/ejcn.2010.98
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind, randomized clinical trial of the effect of ω-3 fatty acids on the oxidative stress of preterm neonates fed through parenteral nutrition

Abstract: Background/Objectives: The aim of this study was to research and draw conclusions about the effect of a parenteral nutrition (PN) fat emulsion, rich in o-3 fatty acids, on the antioxidant markers of preterm infants, when compared with a standard fat emulsion. This was a double-blind, parallel-group study conducted in Athens, Greece, using an equal randomization method. Subjects/Methods: Thirty-eight infants were selected using a double-blind method and a computer-generated randomization list. Both groups recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
142
2
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(150 citation statements)
references
References 28 publications
2
142
2
4
Order By: Relevance
“…30 These findings have prompted researchers to focus their attention on antioxidant supplementations in preterm babies by the use of non-enzymatic proteins, such as transferrin and ferritin, antioxidant enzymes or oxidizable molecules, including vitamins, fatty acids or aminoacids, among others, 26,27 for some of which positive results have been published. 31,32 Interestingly, probiotic microorganism could also play a role as antioxidants, since strains displaying this property have been reported 33 and probiotic metabolites able to prevent the production of proinflammatory cytokines induced by oxidative stress have been recently identified. 34 Therefore, in the context of nutritional interventions the inclusion on infant formula of antioxidants, able to reduce the redox potential also in the while none of the preterm infants was exclusively in breast-feeding.…”
Section: Facultative and Strict Anaerobes In Preterm Neonatesmentioning
confidence: 99%
“…30 These findings have prompted researchers to focus their attention on antioxidant supplementations in preterm babies by the use of non-enzymatic proteins, such as transferrin and ferritin, antioxidant enzymes or oxidizable molecules, including vitamins, fatty acids or aminoacids, among others, 26,27 for some of which positive results have been published. 31,32 Interestingly, probiotic microorganism could also play a role as antioxidants, since strains displaying this property have been reported 33 and probiotic metabolites able to prevent the production of proinflammatory cytokines induced by oxidative stress have been recently identified. 34 Therefore, in the context of nutritional interventions the inclusion on infant formula of antioxidants, able to reduce the redox potential also in the while none of the preterm infants was exclusively in breast-feeding.…”
Section: Facultative and Strict Anaerobes In Preterm Neonatesmentioning
confidence: 99%
“…Eighteen of these studies were RCTs. [11][12][13][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Among nonrandomized studies, 4 were interventional studies with a control group [30][31][32][33] and the remaining 2 studies 8,34 did not test an intervention because they examined the association of BPD with LCPUFA concentrations in blood or in tracheal aspirates. Fifteen RCTs presented dichotomous outcomes.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…Several studies examined .1 neonatal outcome at a time (Table 1). Only a few studies reported other relevant neonatal outcomes, such as number of days of ventilation, or the use or duration of supplementation oxygen, 13,20,22,27,28 patent ductus arteriosus, 12,20,23,[30][31][32] cholestasis, 31,32 or number of days of hospital admission. 8,11,13,18,31,32 Effect Estimates for Dichotomous Neonatal Outcomes…”
Section: Characteristics Of Exposure and Outcomesmentioning
confidence: 99%
“…Ambas, cuando se comparaban con el LCT como única fuente lipídica, tenían la ventaja de ser más estables en las emulsiones de NP (6) generar menor cantidad de peróxidos (ya que esta generación está relacionada con la cantidad de ácidos grasos poliinsaturados [AGPI] y el aporte de vitamina E) y disminuir la producción de ácido araquidónico y sus derivados proinflamatorios debido al menor aporte de ácido linoleico. Actualmente se ha incorporado a estas mezclas aceite de pescado y, en comparación con las de LCT, parece que estas nuevas mezclas generan menor estrés oxidativo (7,8), atenúan la respuesta inflamatoria (9), disminuyen la incidencia de broncodisplasia pulmonar (10), y pueden revertir la colestasis asociada a NP en neonatos (11,12). Sin embargo una revisión Cochrane reciente no encuentra diferencias significativas en la evolución clínica de niños prematuros (13).…”
Section: Lípidosunclassified